A facile and environmentally friendly route to multiferroic nanorods and their size-dependent magnetic properties. Issue 13 (18th February 2015) - Wu, Songping; Lv, Yichao; Lu, Mingjia; Lin, Zhiqun
Abstract : Size-tunable uniform ErMn2 O5 nanorods were synthesized via a surfactant-templated hydrothermal route. They exhibited strong size dependent magnetic properties, that is, a critical length of nanorods for magnetization due to the competition between uncompensated spin and surface strain. Abstract : Multiferroic ErMn2 O5 nanorods have been synthesized via a surfactant-templated hydrothermal route. An environmentally friendly natural surfactant (Arabic gum) has been utilized as a template to prepare ErMn2 O5 nanorods with a controllable morphology and size ( i.e., nanorods with various lengths and basically invariable diameter). ErMn2 O5 nanorods show strong size-dependent magnetic properties that correlate with: (a) a critical length for magnetization, and (b) recognizable divagation between FC and ZFC curves at low temperature. The former could be ascribed to the competition between surface strain and uncompensated spin at the surface, and the latter to Er antiferromagnetic ordering.